What Counts? A Mixed-Methods Study to Inform Evaluation of Shelters for Abused Women. (January 2015) - Wathen, C. Nadine; Harris, Roma M.; Ford-Gilboe, Marilyn; Hansen, Michele
Shelters for abused women have expanded from "safe havens" to providing a range of residential and outreach services, and face increasing pressure to demonstrate "value for money" by providing evaluation metrics that may or may not reflect what they actually do. We conducted interviews and surveys with 68 shelter directors in Ontario, Canada, and found that differences in service philosophy and how abuse is defined influence decisions about who receives services and the shelter's role in the broader community; these in turn affect how the work of shelters is positioned. Implications for shelter service evaluation are discussed.